Bécstől Szentegátig. A Biedermann família uradalmai a Dél-Dunántúlon 1849-1914 - Kaposi, Zoltán (Közép-Európai Közlemények, 2019)
This study examines how a banker family from Vienna ended up in Southern Transdanubia and what role they played in the life of the region. Since several members of the aristocracy were indebted in the first part of the 19th century many of them were forced to sell their lands. This is how the 46040-hectare manor of Üszög and Mozsgó in Baranya and Somogy Counties became the properties of the Vienna based banker family of the Biedermanns. The Biedermanns significantly developed their properties for two generations. Rezső Biedeermann stood out among all who created a model manor at Szentegát at the turn of the century. The manor yielded its results in a relatively poor economic geographical environment; mostly the livestock, forestry and industrial crops were excelling. Members of the family were not only famous for their management. They also carried out many charitable activities. Baron Rezső Biedermann and his wife Elsa Bleichrőder created kindergartens, founded and built schools on their lands. They supported civil society institutions too. Meanwhile, the Biedermanns were living the life of the high society. They spent summers at Szentegát and Abbázia while winters at Vienna and Baden. Their palace at Abbázia was rather famous for welcoming the European political and social leaders quite often.